2011
DOI: 10.1111/j.1751-2980.2011.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pancreatic diabetes in patients with autoimmune pancreatitis

Abstract: OBJECTIVE:Although patients with autoimmune pancreatitis (AIP) tend to have concurrent diverse disorders, very few studies have focused on diabetes mellitus (DM) coexisting with AIP. METHODS:In total 102 AIP patients with DM were divided into three groups. Those with DM before the onset of AIP were labeled group A (n = 35), those who developed DM and AIP simultaneously were labeled group B (n = 58) and those who developed DM after steroid therapy for AIP were labeled group C (n = 9). The characteristics of DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
(82 reference statements)
0
21
0
2
Order By: Relevance
“…A significant implication of AIP is secondary DM. A study conducted in Japan showed a high proportion of micro (retinopathy, nephropathy) and macrovascular complications in patients who had DM prior to the diagnosis of AIP [11].…”
Section: Discussionmentioning
confidence: 99%
“…A significant implication of AIP is secondary DM. A study conducted in Japan showed a high proportion of micro (retinopathy, nephropathy) and macrovascular complications in patients who had DM prior to the diagnosis of AIP [11].…”
Section: Discussionmentioning
confidence: 99%
“…In AIP, disorders of pancreatic exocrine and endocrine function are often present, and DM and IGT are observed in many cases [5][6][7][8] ; this is believed to be due to the effect of both blood flow obstruction of the endocrine gland accompanying formation of exocrine gland brosis and insulitis 18 . We have used aly mice as a mouse model of AIP in previous studies 19 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the involvement of other organs in pancreatitis seems to extend systemically to various organs, suggesting that AIP is an IgG4-related systemic disease 3 4 , with IgG4-related disease 5 recognized as a new entity. In AIP, disorders of both pancreatic exocrine and endocrine function are often induced, and many patients have either diabetes mellitus DM and/or impaired glucose tolerance IGT [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…A lrededor de 60-70% de los pacientes con pancreatitis autoinmune (PAI) presenta diabetes mellitus (DM) y su diagnóstico es simultáneo en más de 50% de ellos 1,2 . Presentamos el caso de un paciente adulto mayor que debuta con DM, en contexto de la aparición de un cuadro compatible con PAI, experimentando una notable mejoría de su control metabólico con la terapia esteroidal de su enfermedad pancreática.…”
unclassified